Control of basal jasmonate signalling and defence through modulation of intracellular cation flux capacity. Issue 4 (8th September 2017) - Lenglet, Aurore; Jaślan, Dawid; Toyota, Masatsugu; Mueller, Matthias; Müller, Thomas; Schönknecht, Gerald; Marten, Irene; Gilroy, Simon; Hedrich, Rainer; Farmer, Edward E.
Summary: Unknown mechanisms tightly regulate the basal activity of the wound‐inducible defence mediator jasmonate (JA) in undamaged tissues. However, the Arabidopsis fatty acid oxygenation upregulated2 ( fou2 ) mutant in vacuolar two‐pore channel 1 (TPC1 D454N ) displays high JA pathway activity in undamaged leaves. This mutant was used to explore mechanisms controlling basal JA pathway regulation. fou2 was re‐mutated to generate novel ' ouf ' suppressor mutants. Patch‐clamping was used to examine TPC1 cation channel characteristics in the ouf suppressor mutants and in fou2 . Calcium (Ca 2+ ) imaging was used to study the effects fou2 on cytosolic Ca 2+ concentrations. Six intragenic ouf suppressors with near wild‐type (WT) JA pathway activity were recovered and one mutant, ouf8, affected the channel pore. At low luminal calcium concentrations, ouf8 had little detectable effect on fou2 . However, increased vacuolar Ca 2+ concentrations caused channel occlusion, selectively blocking K + fluxes towards the cytoplasm. Cytosolic Ca 2+ concentrations in unwounded fou2 were found to be lower than in the unwounded WT, but they increased in a similar manner in both genotypes following wounding. Basal JA pathway activity can be controlled solely by manipulating endomembrane cation flux capacities. We suggest that changes in endomembrane potential affect JA pathway activity.